Wspólnotowa polityka przedsiębiorczości a koncepcja rozwoju opartego na powiązaniach typu klastrowego - Rosińska, Magdalena (The European Union enterprise policy and the concept of development basing on cluster type connections, 2006)
The paper is an attempt to present the concept of development based on the cluster type connections as a possible method of creating favourable environment for SMEs. The author comments on the EU common enterprise policy - its principal objectives and framework. Then she discusses the idea of cluster type connections as a mechanism for the growth of market actors’ competitiveness and regional development. The EU policy of the SMEs promoting is one of the elements of single market creation. By generating the new possibilities of large scale market participation these activities simultaneously make local actors the subjects of increasing competitiveness. The support programmes were to facilitate this challenge. The regional funds, which provide funds for easier access to services, business networking and innovation, play a significant role in this venture. In order to improve competitiveness this type of support promotes local systems of business co-operation. The creation of cluster type connections, based on SMEs from regions, seems to be the ideal way to foster entrepreneurial spirit. The last part of the paper presents clusters in Europe - variety of their activities and support systems. The aim of the account is to assess development perspectives while taking into consideration the available EU sources and under various theoretical concepts.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1129, s. 289-297